Security Externalities of the Chinese Maritime Silk Road Initiative in the Indian Ocean, with Focus on Sino-Indian Competition - Burešová, Hana (2019)
The goal of this thesis is to provide a clearer understanding of the consequences – here especially security externalities – of the development along the Chinese Maritime Silk Road in the Indian Ocean. There are two aspects of this issue, firstly how Maritime Silk Road Initiative affects small economies perceived by China as strategic, and secondly the threats and opportunities of the Maritime Silk Road and String of Pearls in the waters of Indian Ocean.